Effect of Anionic Antimicrobial Peptides on model lipid membranes - Noe, Melania Macarena (2023)
Anionic antimicrobial peptides (AAPs) were first described in the early 1980s. They have been identified as part of the innate immune system of vertebrates, invertebrates and plants and are active against bacteria, fungi, viruses and pests such as insects. Membrane interaction appears to be key to the antimicrobial function of AAMPs. In the present work, we use the anionic peptide β-lg125-135, obtained from the tryptic hydrolysate of β- lactoglobulin, and evaluate its interaction with model membranes. We use DPPC or DPPC:DPPG mixtures as models of eukaryotic and bacterial membranes, respectively. In previous work we have shown that β-lg125-135 interacts preferentially with anionic monolayers. In the present work we investigate the effect of β-lg125-135 on membrane order and permeability. Unilamellar vesicles were used as model membranes. DPH and TMA-DPH fluorescence anisotropy were used to evaluate the effect of peptide interaction on membrane order: The DPH probe detects the hydrocarbon region, whereas the fluorescent probe TMA-DPH, with an additional charged group, is anchored at the lipid/ water interface and reports on a bilayer region distinct from that of the hydrophobic DPH, which detects a deeper region. The results obtained show that for vesicles composed of the equimolar lipid mixture, the anisotropy of both probes tested increases in the presence of peptide. For dpPC vesicles, this effect was less pronounced at the temperatures tested. This would indicate that the peptide partitions into the lipid mixing bilayers, increasing the molecular order. The effect of peptide-membrane interaction on vesicle permeability was assessed as the release of carboxyfluorescein entrapped in liposomes. We measured the increase in carboxyfluorescein fluorescence intensity with increasing AAP concentrations to elucidate the relationship between bilayer disruption and lipid bilayer perturbation. The results obtained showed that the higher the peptidelipid molar ratio, the higher the percentage of release of the fluorescent probe.